1975
DOI: 10.1128/aac.7.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonoacetic Acid-Resistant Herpes Simplex Virus Infection in Hairless Mice

Abstract: Phosphonoacetic acid (PAA)-resistant type 1 herpes simplex virus population was isolated by repeated passage of the virus in the presence of this inhibitor. Hairless mice infected percutaneously with the inhibitor-resistant or the parental inhibitor-susceptible virus were treated intraperitoneally with PAA and 9-β- d -arabinofuranosyl-adenine by using several different dosage schedules. Whereas 9-β- d -arabinofuranosyl-adenine was effective both in the PAA-suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 11 publications
6
32
1
Order By: Relevance
“…DISCUSSION The selection of PFA' HSV mutants can be achieved in cell cultures and is an indication of the specificity of the inhibitor (6). The ease of selecting resistant mutants (Tables 1 and 2) was similar for PFA and PAA and corresponds to earlier reports for PAA (3,7,11) and idoxuridine (2). Resistance development seems, however, to be much easier in cell culture than in animals, qs reported for PAA (3) and idoxuridine (9), or found clinically with idoxuridine (8).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…DISCUSSION The selection of PFA' HSV mutants can be achieved in cell cultures and is an indication of the specificity of the inhibitor (6). The ease of selecting resistant mutants (Tables 1 and 2) was similar for PFA and PAA and corresponds to earlier reports for PAA (3,7,11) and idoxuridine (2). Resistance development seems, however, to be much easier in cell culture than in animals, qs reported for PAA (3) and idoxuridine (9), or found clinically with idoxuridine (8).…”
Section: Resultssupporting
confidence: 55%
“…The mechanism for this is unclear. It has been reported that PAA-resistant HSV infections in mice can be treated with vidarabine as effectively as the HSV wild type (11). The animal models might not be so precise as to determine minor changes in drug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Amino Acid Residues phonoformate (PFA) where it is relatively easy to select resistant mutants (Klein and Friedman-Klein, 1975;Hay and SubakSharpe, 1976;Honess and Watson, 1977;Eriksson and Oberg, 1979;Derse et al, 1982). One possible explanation is that PAA and PFA exert additional effects resulting in an increased mutation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with PAA (400 mg/kg) by the same route resulted in 46.7% survivors, with an MST of about 16 days, whereas 13.3% of the salinetreated animals survived, and the MST was 10.5 days. The ara-A and PAA concentrations used for subcutaneous treatment were previously shown to be effective in HSV-infected hamsters (32) and mice (18,31), respectively.…”
Section: Resultsmentioning
confidence: 99%